HTLV-I associated myelopathy in Brazil: a preliminary report - L. H. Martins Castro; Cláudia J Chaves; D. Callegaro; J. P. S. Nóbrega; M. Scaff (Arquivos de Neuro-Psiquiatria)
In this preliminary report the authors present the finding of a high prevalence (37.5%) of seropositivity of antibodies to HTLV-I tested by Western blotting in a sample of 16 Brazilian patients with chronic myelopathies of undetermined origin.